Hydrological responses to climate and land use changes: the paradox of regional and local climate effect in the Pra River Basin of Ghana (2020)
Study Region: Pra River Basin, Ghana. Study Focus: The study modelled the changes in water yield using regional, sub-regional and local climate conditions from modelling outputs at spatial resolutions of 44 km, 12 km and 0.002 km respectively to drive the Integrated Valuation of Ecosystem Services and Trade-offs model at three time periods of land use land cover (LULC). Changes in historical water yield (simulated for 1986, 2002 & 2018 LULC using the mean climatic parameters from 1981-2010) and future scenario (simulated for 2018 LULC using the mean climatic parameters from 2020-2049) for annual, seasonal and monthly periods were assessed. New Hydrological Insights for the Region: The results show that future annual water yield could change by -46%, -48%, +44% and -35% under the regional, sub-regional, local and ensemble mean of the climate scenarios respectively. Seasonal water yield from the ensemble mean of the future climate scenario was projected to decrease between 2-16 mm, with a mean decrease of 33.39% during the December–February season. There was no directional effect of spatial resolution on water yield. The future period could be impacted by both drought and flood. We recommend that re/afforestation should be encouraged to improve infiltration and reduce deforestation which was 2.27% per annum in the assessed period to prevent flood causing runoffs, while irrigation technology will help to improve resilience to drought.